The Role of Land Titles Registrar in the Imposition of Taxes on Acquisition of Rights on Inherited Land and Buildings According to Islamic Law - Setiyowati Setiyowati; Edy Lisdiyono; Noor Wachida (APPTHI, 2019)
Tax on Acquisition of Land and Building Rights (Pajak Perolehan Hak atas Tanah dan Bangunan/BPHTB) is a tax that is imposed or must be paid by the taxpayer in connection with the transfer of Land and Building Rights. In Islam, the existence of heirs and heirs is regulated in the Qur’an contained in Sura al-Nisa. Inherited assets in the form of land and buildings, which are the right of heirs, can be owned by one of the heirs by buying or paying the other heirs. It is stated in the Deed of Sharing of Joint Rights (Akta Pembagian Hak Bersama/APHB) made by the Land Deed Making Official (Pejabat Pembuat Akta Tanah/PPAT). The results showed: 1) According to Islamic law, the calculation of the amount of BPHTB tax is not the same as the amount of tax calculated based on Law No. 20 of 2000 concerning Customs for Acquisition of Rights on Land and Buildings; this is related to the determination of the amount of inheritance received, where the amount depends on the number of inheritance rights holders and their gender and nasab and religious relationships. 2) The process of determining the number of taxpayers in the Customs Tax on Land and Building Rights, which is associated with tax validation, often creates uncertainty, both the transaction value can change, and the calculation and the amount of tax that must be paid by the taxpayer this is because the Regional Revenue Agency (Badan Pendapatan Daerah/BAPENDA) local does not have a fixed reference. PPAT’s role is to help calculate the amount of the BPHTB tax and pay it to the tax office. Abstrak Pajak Perolehan Hak atas Tanah dan Bangunan (BPHTB) adalah pajak yang dikenakan atau harus dibayar oleh Wajib Pajak sehubungan dengan peralihan Hak atas Tanah dan Bangunan. Dalam Islam, keberadaan ahli waris dan ahli waris diatur dalam Alquran yang tertuang dalam Surah al-Nisa. Harta warisan berupa tanah dan bangunan yang menjadi hak ahli waris dapat dimiliki oleh salah satu ahli waris dengan cara membeli atau membayar kepada ahli waris lainnya, hal ini dituangkan dalam Akta Pembagian Hak Bersama (APHB) yang dibuat oleh Pejabat Pembuat Akta Tanah (PPAT). Pembahasan: 1) Menurut hukum Islam perhitungan besarnya pajak BPHTB tidak sama dengan besarnya pajak yang dihitung berdasarkan Undang-Undang Nomor 20 Tahun 2000 tentang Kepabeanan Perolehan Hak atas Tanah dan Bangunan, hal ini terkait dengan penentuan besarnya harta warisan yang diterima, dimana besarnya tergantung dari banyaknya pemegang hak waris dan jenis kelamin serta hubungan nasab dan agamanya. 2) Proses penetapan jumlah wajib pajak dalam Bea Cukai Hak atas Tanah dan Bangunan yang dikaitkan dengan pengesahan pajak seringkali menimbulkan ketidakpastian, baik nilai transaksi dapat berubah, penghitungan maupun besarnya pajak yang harus dibayar oleh wajib pajak hal ini karena Badan Pendapatan Daerah (BAPENDA) setempat tidak memiliki acuan tetap. Peran PPAT adalah membantu menghitung besaran pajak BPHTB dan menyetorkannya ke kantor pajak. Kata kunci: Pejabat Pembuat Akta Tanah, Warisan, Hukum Islam, Perolehan Hak atas Tanah dan Bangunan